Kualitas Disain dan Substansi Materi Program Multimedia Interaktif: Kajian Evaluasi Formatif - Elang Krisnadi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This study aims to determine the quality of the material and design of the interactivemultimedia program (PMI) with the topic of Napier's Bone props in terms of content feasibility,learning design, display design by experts, and by students in one-on-one evaluation activities,small group evaluation, as well as field trials. The study by experts and students was carried outusing an instrument specifically developed for formative evaluation activities, then followed upby conducting interviews. The results showed that the learning process packaged in PMI had beenpresented very well and valid. In terms of relevance, accuracy, and depth, the material is alreadyrelevant to the topic and competence. From the aspect of instructional design, the packaging ofthe PMI presentation according to the assessment of the instructional design expert is good and isin accordance with the achievement of learning objectives. The presentation of the material hasbeen arranged in the right mode and there is balance and appropriateness in the use of text,animation, graphics, sound, and video elements. Meanwhile, from one-on-one evaluationactivities, small group evaluations, as well as during field trials, overall information was obtained,the learning process delivery techniques presented through PMI were interesting